PERAN ANGGOTA KELUARGA DALAM PEMILIHAN RESTORAN DI KAWASAN PUNCAK, KABUPATEN BOGOR - Rahmat Ingkadijaya; Bunasor Sanim; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2007)
The purpose of this research are (1) to analyze the roles of familiy members in choosing restaurant, (2) to analyze restaurant attributes perceived as the most important one by each family members, and (3) to make managerial recommendation for marketing restaurants in Puncak area, Bogor Regency. This research used descriptive method and involved 141 respondents. The respondents were members of family who were eating in restaurants along street in Puncak area were result showed that children is roles were as initiator, gatekeeper, dan influencer. The roles of mother were more flexible because she had roles as initiator, gatekeeper, influencer and decider. Father had only one role but very important that was as decider. Restaurant attributes that became priority were taste of food and beverage, food hygien and sanitation, and the cleanliness of restaurant. Perception of father, mother, and children about those attributes were the same.